The Influence of Safety on Tourists’ Visiting Decisions to Pantai Binasi, Kota Pariaman - Rima Melati; Kurnia Illahi Manvi (Journal of Multidimensional Management, 2025)
This study investigates the influence of perceived safety on tourists’ visiting decisions to Pantai Binasi, Kota Pariaman, a coastal destination facing security-related concerns such as local harassment and lack of environmental monitoring. Using a quantitative, causal-associative approach, data were gathered from 100 visitors through incidental sampling and analyzed using descriptive statistics and simple linear regression via SPSS 26. The safety variable was rated moderately (mean = 3.13; TCR = 62.58%), while the visiting decision also received a moderate score (mean = 3.15; TCR = 62.98%). Regression results show that perceived safety has a significant positive effect on visiting decisions (p < 0.001), with a determination coefficient (R²) of 0.572, indicating that 57.2% of the variation in tourist decisions is explained by perceived safety. These findings highlight the critical role of safety in tourism behavior and underscore the need for improved destination management strategies, particularly in enhancing physical security, mitigating local disturbances, and providing clear safety signage to foster a more trustworthy and welcoming environment for visitors.